Sea - Laita, Mark (Abrams in association with PQ Blackwell, 2011)
"With cutting-edge photographic techniques, Mark Laita unveils the full splendor and other-worldliness of the ocean's inhabitants in an entirely new and thrilling way"-- Provided by publisher